Ba1−xSrxCe0.8−yZryY0.2O3−δ protonic electrolytes synthesized by hetero-composition-exchange method for solid oxide fuel cells. (24th August 2017) - Lee, Kan-Rong; Tseng, Chung-Jen; Chang, Jeng-Kuei; Wang, Kuan-Wen; Huang, Yu-Shuo; Chou, Tzu-Chi; Chiu, Kuo-Chuang; Tsai, Li-Duan; Lee, Sheng-Wei
Abstract: This study reports the synthesis of proton-conducting Ba0.8 Sr0.2 Ce0.6 Zr0.2 Y0.2 O3−δ oxides by using a combination of the sol–gel process and hetero-composition-exchange technique. The experimental results show that the sintered Ba0.8 Sr0.2 Ce0.6 Zr0.2 Y0.2 O3−δ pellet synthesized by the hetero-composition-exchange method exhibits excellent sinterability, good relatively density, and high protonic conduction. Furthermore, the Pt/electrolyte/Pt single cell with such an electrolyte shows a significantly higher maximum power density as compared to those oxides prepared from conventional sol–gel powders. Based on the experimental results, we attempt to explain the improvement mechanism in terms of as-calcined particle characteristics and proton hopping distance. This work shows that the Ba1−x Srx Ce0.8−y Zry Y0.2 O3−δ oxides synthesized by the sol–gel combined with hetero-composition-exchange method would be a promising electrolyte for H + -SOFC applications. More importantly, this new fabrication approach could be applied to other similar perovskite-type electrolyte systems. Highlights: This study first synthesizes the Ba0.8 Sr0.2 Ce0.6 Zr0.2 Y0.2 O3−δ oxides by HCE. The HCE method improves the sinterability, uniformity, and protonic conduction. The Pt/electrolyte/Pt shows a significantly higher maximum power density. This new approach could be applied to other similar perovskite material systems.